1977
DOI: 10.1159/000207874
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Mononucleosis in Hodgkin’s Disease

Abstract: A patient who developed infectious mononucleosis while being treated for Hodgkin’s disease is presented. This pathological profile does not support the concept of a causal relationship between Epstein-Barr virus and Hodgkin’s disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1979
1979
1989
1989

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Thus, several investigators have found higher titres of EBV-antibodies in patients with H D than in healthy controls (Henle and Henle, 1973;Langenhuysen et al, 1974;Hesse et al, 1977), but this may be due to the inability of patients with H D to control chronic latent infections with herpesvirus. Moreover, EBV-antibodies are not found in all patients with HD, and some studies have shown similar proportion of past EBV infection in patients with H D as compared to appropriate controls (Goldman and Aisenberg, 1970 Davidson and Lessels, 1977). However, H D may be a heterogenous disease, and if EBV plays a role in the aetiology of the disease, it can obviously be of importance only in a proportion of the patients with HD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, several investigators have found higher titres of EBV-antibodies in patients with H D than in healthy controls (Henle and Henle, 1973;Langenhuysen et al, 1974;Hesse et al, 1977), but this may be due to the inability of patients with H D to control chronic latent infections with herpesvirus. Moreover, EBV-antibodies are not found in all patients with HD, and some studies have shown similar proportion of past EBV infection in patients with H D as compared to appropriate controls (Goldman and Aisenberg, 1970 Davidson and Lessels, 1977). However, H D may be a heterogenous disease, and if EBV plays a role in the aetiology of the disease, it can obviously be of importance only in a proportion of the patients with HD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, EBV-antibodies are not found in all patients with HD, and some studies have shown similar proportion of past EBV infection in patients with H D as compared to appropriate controls (Goldman and Aisenberg, 1970;Henle and Henle, 1973;Langenhuysen et al, 1974;Hesse et al, 1977;Lange et al, 1978). A few cases of IM in patients with H D have also been reported (Kenis et at., 1958;Langenhuysen, 1976;Davidson and Lessels, 1977). However, H D may be a heterogenous disease, and if EBV plays a role in the aetiology of the disease, it can obviously be of importance only in a proportion of the patients with HD.…”
Section: Discussionmentioning
confidence: 99%
“…Both Hodgkin's disease and infectious mononucleosis occur preferentially in higher socioeconomic groups, for example (McMahon 1966;Gutensohn and Cole 1981), and the possibility of an independent association on this basis arises. Not all patients with Hodgkin's disease possess antibodies to EBV [infectious mononucleosis following Hodgkin's disease has been reported (Davidson and Lessles 1977)]; and whereas some patients with Hodgkin's disease may have elevated anti-VCA and anti-EBNA titres, this characteristic appears to be secondary to immunosuppression rather than indicating a direct association between Hodgkin's disease and EBV infection (Hesse et al 1977;Mochanko et al 1979). Neither EBV DNA nor EBNA has been detected in Hodgkin's tissue or cultured Reed-Sternberg cells (Nonoyama et al 1974;Gallo and Geimann 1981).…”
Section: Infectious Mononucleosis and Hodgkin's Diseasementioning
confidence: 99%
“…Although in many cases of HD serum titers against EBV are somewhat increased [4,5], some cases of HD show no antibody evidence of EBV infection. Serious doubts as to any specific role for EBV in HD come from cases with established HD in which IM occurred during the course of the disease [6,7]. The purpose of this communication is to show by DNA analysis of the tumor cells-searching for EBV genomes--that, although HI) developed shortly alter IM and antibody response to EBV was compatible with the convalescent phase of IM, EB-viral infection most likely may not be directly oncogenic but rather may contribute to an immunologic state which in turn predisposes to malignancy.…”
Section: Hodgkin's Disease Mononucleosismentioning
confidence: 99%